Trophoblastic disease - L. A. Meshcheryakova (ABV-press, 2015)
Trophoblastic disease encompasses a group of trophoblast abnormalities always associated with pregnancy. The urgency of studying the problemof the diagnosis and treatment of this pathology is clear because of the young age of patients, the high efficiency of treatment for malignant forms of the disease even in distant metastases and the possibility of their complete cure in 98 % of the patients with preserved reproductive function. The keystone of success is the correct and timely diagnosis of the disease and current highly effective treatment in the specialized clinic having all diagnostic facilities and successful experience in treating these patients. Clinicians» knowledge of the problem allows the avoidance of frequent errors both in the diagnosis and choice of treatment policy for patients with malignant trophoblastic tumors that may be fatal for some patients. The paper illustrates theoretical aspects with the results of treatment in patients at the N. N. Blokhin Russian Cancer Research Center that is an expert in the diagnosis and treatment of trophoblastic tumors in Russia. The paper deals with the diagnosis, treatment, and monitoring of trophoblastic disease.